The Presence of Aflatoxin M(1) in Milk and Milk Products in Bangladesh - Sumon, Abu Hasan (Toxins (Basel), 2021)
As milk provides both micro- and macronutrients, it is an important component in the diet. However, the presence of aflatoxin B(1) (AFB(1)) in the feed of dairy cattle results in contamination of milk and dairy products with aflatoxin M(1) (AFM(1)), a toxic metabolite of the carcinogenic mycotoxin. With the aim to determine AFM(1) concentrations in milk and milk products consumed in Bangladesh, in total, 145 samples were collected in four divisional regions (Sylhet, Dhaka, Chittagong, and Rajshahi). The samples comprised these categories: raw milk (n = 105), pasteurized milk (n = 15), ultra-high temperature (UHT)-treated milk (n = 15), fermented milk products such as yogurt (n = 5), and milk powder (n = 5). AFM(1) levels in these samples were determined through competitive enzyme-linked immunosorbent assay (ELISA). Overall, AFM(1) was present in 78.6% of milk and milk products in the range of 5.0 to 198.7 ng/L. AFM(1) was detected in 71.4% of raw milk (mean 41.1, range 5.0–198.7 ng/L), and in all pasteurized milk (mean 106, range 17.2–187.7 ng/L) and UHT milk (mean 73, range 12.2–146.9 ng/L) samples. Lower AFM(1) levels were found in yogurt (mean 16.9, range 8.3–41.1 ng/L) and milk powder samples (mean 6.6, range 5.9–7.0 ng/L). About one-third of the raw, pasteurized, and UHT milk samples exceeded the EU regulatory limit (50 ng/L) for AFM(1) in milk, while AFM(1) levels in yogurt and milk powder samples were well below this limit. Regarding regions, lower AFM(1) contamination was observed in Chittagong (mean 6.6, max 10.6 ng/L), compared to Sylhet (mean 53.7, max 198.7 ng/L), Dhaka (mean 37.8, max 97.2 ng/L), and Rajshahi (mean 34.8, max 131.4 ng/L). Yet, no significant difference was observed in AFM(1) levels between summer and winter season. In conclusion, the observed frequency and levels of aflatoxin contamination raise concern and must encourage further monitoring of AFM(1) in milk and milk products in Bangladesh.